Penerapan Head Up 30 Derajat Pada Pasien Intracerebral Hemorrhage Diruang Icu Rumah Sakit TK III DR R Soeharsono Banjarmasin - Ernawati; Ariani , Sri Purwanti; Nor Aina (Jurnal Sains Farmasi Dan Kesehatan, 2024)
Degenerative diseases are non-communicable diseases that occur due to a decline in organ function and aging. The primary cause of degenerative diseases is an unhealthy diet. The theories associated with degenerative diseases include free radicals and growth inhibition. One such degenerative disease is Stroke. Stroke is a cerebrovascular disease. According to the World Health Organization (WHO), Stroke is a condition characterized by the rapid development of clinical signs, including focal and global neurological deficits, which can worsen and persist for 24 hours or more, and can cause death, with no other clear cause except vascular involvement.